Spontaneous Macular Hole Closure after Valsalva Retinopathy and Nd:YAG Laser Treatment - Elcin Suren; Melih Akidan; Muhammet Kazim Erol; Devrim Toslak (Case Reports in Ophthalmological Medicine)
Purpose. The purpose of this report is to present a case who had spontaneous macular hole closure after Nd:YAG laser membranotomy applied to premacular haemorrhage associated with Valsalva retinopathy. Methods. Case report. Results. A 19-year-old young male patient presented to our clinic with sudden vision loss in his right eye, which had occurred 2 weeks before, following push-up and sit-up exercise. The patient was found to have premacular haemorrhage associated with Valsalva retinopathy. Nd:YAG laser membranotomy was performed. During his follow-up at week 1, full-thickness MH was observed and he was put under observation. At month 6, his vision acuity improved, laser coagulation sites in the fundus disappeared, and macular hole closed spontaneously. Conclusion. Macular hole that develops after Nd:YAG laser treatment of Valsalva retinopathy may spontaneously be closed like in our case. However, there is a need for further research to understand the mechanism of closure.